Making clinical teaching visible—A time and motion study of hospital rounds in undergraduate medical teaching - Kilian, Paddy; Alshehabi, Nagam; Othman, Malek; Mahmoud, Anan; du Preez, Leon; Zary, Nabil; Ho, Samuel B. (Frontiers in Medicine, 2024)
Background: Teaching medical students in the clinical setting is frequently perceived as a demanding commitment by attending physicians. There is a paucity of data measuring the duration and efficacy of teaching during clinical rounds. Aim: The aim of this study was to assess both the quantity and quality of clinical teaching time dedicated to medical students on hospital ward rounds. Methods: A cross-sectional direct structured observational study was conducted during the morning rounds of attending physicians involved in teaching undergraduate medical students at three different clinical facilities in three different specialties. A validated observational tool was used by four observers to record teaching time and quality indicators. Results: In terms of teaching duration, it was observed that 25% of the total morning round time was allocated to teaching. However, this measure varied widely between different physicians and specialties. As for teaching quality, actions categorized as active teaching by the teachers were observed in 19% of the interactions observed per round, while active learning by the students was observed in 17% interactions per round. Teacher high-cognition interactions were similarly observed in 23% of actions per round, while student high-cognition interactions occurred in 16% of actions per round. Internal Medicine tended to score higher than both Pediatrics and Surgery in terms of percentage teaching time as well as percentage of active teaching observed per round. Using liberal criteria, rounds characterized overall as predominantly active or high-cognition by both teachers and students were observed in only 21% of the total number of rounds observed. Conclusion: These results indicate that the percentage of teaching time during ward rounds is highly variable, and that round teaching generally consists of passive and low-cognition interactions. Future work is needed to train clinical faculty to achieve a desired level of teaching quality, and to determine if there are any changes in teaching time commitments and student outcomes.